Comparable efficacy with varying dosages of glucarpidase in pediatric oncology patients. Issue 9 (28th January 2015) - Scott, Jeffrey R.; Zhou, Yinmei; Cheng, Cheng; Ward, Deborah A.; Swanson, Hope D.; Molinelli, Alejandro R.; Stewart, Clinton F.; Navid, Fariba; Jeha, Sima; Relling, Mary V.; Crews, Kristine R.
<x xml:space="preserve">Abstract</x> Background Glucarpidase rapidly reduces methotrexate plasma concentrations in patients experiencing methotrexate‐induced renal dysfunction. Debate exists regarding the role of glucarpidase in therapy given its high cost. The use of reduced‐dose glucarpidase has been reported, and may allow more institutions to supply this drug to their patients. This report explores the relationship between glucarpidase dosage and patient outcomes in pediatric oncology patients. Methods The authors evaluated data from 26 patients who received glucarpidase after high‐dose methotrexate. Decrease in plasma methotrexate concentrations and time to renal recovery were evaluated for an association with glucarpidase dosage, which ranged from 13 to 90 units/kg. Results No significant relationship was found between glucarpidase dosage (units/kg) and percent decrease in methotrexate plasma concentrations measured by TDx (P > 0.1) or HPLC (P > 0.5). Patients who received glucarpidase dosages <50 units/kg had a median percent reduction in methotrexate plasma concentration of 99.4% (range, 98–100) measured by HPLC compared to a median percent reduction of 99.4% (range, 77.2–100) in patients who received ≥50 units/kg. Time to SCr recovery was not related to glucarpidase dosage (P > 0.8). Conclusions The efficacy of glucarpidase in the treatment of HDMTX‐induced kidney injury was not dosage‐dependent in this retrospective analysis of pediatric oncology patients. Pediatr Blood Cancer 2015;62:1518–1522. © 2015 Wiley Periodicals, Inc.